El derecho a la desconexión digital como norma permanente, una garantía al descanso diario y al disfrute del tiempo libre - Rivera Quintana, Susan Catherine (2024)
Technological advances have been covering the different countries of the world and the use of technologies brought changes to companies and also for labor relations. Due to its great connectivity, ICTs are coming to affect the recognized rights of workers, such as the limit of the working day and rest, promoting the incorporation of the "Right to disconnection" in various legislations. The purpose of this research is to determine the reasons why our legislation should adopt the right to disconnection as a permanent legal norm despite the normative presence of the right to rest and the limit of the working day, in order to guarantee workers physical and mental recovery through adequate daily rest. For this purpose, a descriptive analysis of the technological evolution in the world and at national level is carried out, in addition to its repercussion in the companies as in the workers, a review is made of the national and international regulations on a working day, the right to rest and the enjoyment of free time, reflecting on the physical and psychological effects resulting from long working hours, carrying out a comparative analysis of the "Right to disconnection" implemented in other countries to finally review the evolution of national regulations in what regards this right. Due to its relevance, it is considered necessary to regulate the right to digital disconnection through a specific standard, as a “means” through which workers are guaranteed due rest in the face of hyperconnectivity or the impossibility of refusing to follow orders after the end of their working day.